VEHICLE OPERATING COST OF EXPRESS BUSES (PATAS) IN JAKAR - Agung Nugroho, Putro
This research describes an investigation of the vehicle operating cost of express buses in Jakarta. A major emphasis of this study was applying a regression approach to obtaining mathematical models of the effects of vehicle age on operating cost components on some routes. There are three route categories in this research, based on route length namely: Route I (?18 Km), Route II(18<x<22Km)and Route III (?22Km). The cost components considered in the analysis were fuel, retribution fee, lubricant, tires, spareparts, maintenance, wages, license, depreciation and overhead. The results of this research found relationships between vehicle age and operating cost components. The optimum kilometerage is the age which has a minimum total vehicle operating cost. If depreciation cost was excluded from total vehicle operating cost then the optimum kilometerage was not obtained. However if depreciation cost was included in total vehicle operating cost then the optimum kilometerages were : - Route I at age 16.6 years. - Route II at age 17 years - Route III at age 18 years. The financial performance is a measure of the profitability of each route and is calculated as revenue per day divided by operating cost per day. The lowest value of financial performance on Route I was 0.87, for Blok M - Senen route (P42), and the highest value on Route I was 2.17 for Pulau Gadung - Grogol route (P7). The lowest value of financial performance on Route II was 0.75, for Kampung Rambutan - Blok M route (P15), while the highest performance was 1.89, for Pulau Gadung - Blok M route (P4). The lowest value of financial performance on Route III was 0.72, for Blok M - Tanjung Priok route (P3d), while the highest value was 1.73, for Tanjung Priok - Kampung Rambutan route (P8A).